Distance-time graph recorder - Santos, Sergio Salvador 1940-
This study focuses on the design, construction, and use of a distance-time graph recorder, a device for the study of linear motion in bodies. This device directly plots the distance-time graph of a moving body. It was designed for experiments/ demonstrations on linear motion which will help students learn the processes of science and some concepts in physics as well.